Effect of COL5A1, GDF5, and PPARA genes on a movement screen and neuromuscular performance in adolescent team sport athletes - Stastny, P.; Lehnert, M.; De Ste Croix, M.; Petr, M.; Svoboda, Z.; Maixnerova, E.; Varekova, R.; Botek, M.; Petrek, M.; Lenka, K.; Cieszczyk, P. (The Journal of Strength and Conditioning Research, 2019)
The risk of injury increases with adolescents' chronological age and may be related to limited muscle function neuromuscular, genetic, and biomechanical factors. The purpose of this study was to determine whether COL5A1, PPARA, and GDF5 genes are associated with muscle functions and stretch-shortening cycle performance in adolescent athletes. One hundred forty-six youth players (14.4 ± 0.2 years) from various team sports (basketball n = 54, soccer n = 50, handball n = 32) underwent a manual test for muscle function, maturity estimation, functional bend test (FBT), passive straight leg raise (SLR) test, leg stiffness test, test of reactive strength index (RSI), and gene sampling for COL5A1, PPARA, and GDF5. The x2 test did not show any differences in allele or genotype frequency between participants before and after peak height velocity. Multivariate analysis of variance showed that COL5A1 rs12722 CT heterozygotes had worse score in FBT (p < 0.001), worse score in SLR (p = 0.003), and lower maturity offset (p = 0.029, only in females) than TT homozygotes. Male GDF5 rs143383 GG homozygotes showed better score in SLR than AA and AG genotypes (p = 0.003), and AA and AG genotypes in both sex had greater RSI than GG homozygotes (p = 0.016). The PPARA rs4253778 CC homozygotes had greater RSI than GG and GC genotypes (p = 0.004). The CT genotype in COL5A1 rs12722 is possible predictor of functional movement disruption in the posterior hip muscle chain, causing shortening in FBT and SLR, which includes hamstrings function. CT genotype in COL5A1 rs12722 should be involved in programs targeting hamstring and posterior hip muscle chain.